Experimental Study of Cooling Performance and Electrical Parameters in a Microcontroller-Driven Inverter AC System - Negara, I Gede Artha; Anakottapary, Daud Simon; Midiani, Luh Putu Ike; Temaja, I Wayan; Santosa, I Dewa Made Cipta (Universitas Negeri Padang, 2023)
Recent advancements in air conditioning (AC) technologies, such as inverters, enable the compressor to remain activated despite reaching the setpoint temperature. This study investigates the cooling performance and electrical parameters of a split inverter AC system controlled by a microcontroller in order to determine the operational performance characteristics of the air conditioning system. An ATmega 2560 microcontroller integrated with PZEM, DS18B20, and LCD I2C sensors monitors was 8,525 Btu/h capacity split inverter AC. During a 1-hour experimental run, the temperature differential between supply air (Tsupply) and return air (Treturn) stabilized at approximately 17 °C, with Tsupply reaching a minimum of 8.5 °C. Treturn remained relatively constant after 500 s with no fluctuations. Moreover, power draw maintained an average of 750 W (1 PK) with no variations, exhibiting an inverse relationship with Tsupply. The maximum energy consumption recorded during the experiment was 1,373 kWh. As expected based on fundamental thermodynamic principles, the energy usage showed a direct proportional relationship with the total runtime of the system. That is, the longer the AC system was engaged, the higher the total energy required to maintain the cooling effect. Overall, microcontroller-based split inverter AC enables real-time performance monitoring and efficient operation, representing a promising technology.